Inspiratory muscle strength training to improve cardiometabolic health in patients with type 2 diabetes mellitus: protocol for the diabetes inspiratory training clinical trial - Reed, Baylee L.; Tavoian, Dallin; Bailey, E. Fiona; Funk, Janet L.; Coletta, Dawn K. (Frontiers in Endocrinology, 2024)
Type 2 diabetes mellitus (T2DM) is a complex, chronic metabolic disease that carries with it a high prevalence of comorbid conditions, making T2DM one of the leading causes of death in the U.S. Traditional lifestyle interventions (e.g., diet, exercise) can counter some adverse effects of T2DM, however, participation in these activities is low with reasons ranging from physical discomfort to lack of time. Thus, there is a critical need to develop novel management strategies that effectively reduce cardiometabolic disease risk and address barriers to adherence. High-resistance inspiratory muscle strength training (IMST) is a time-efficient and simple breathing exercise that significantly reduces systolic and diastolic BP and improves vascular endothelial function in adults with above-normal blood pressure. Herein we describe the study protocol for a randomized clinical trial to determine the effects of a 6-week IMST regimen on glycemic control and insulin sensitivity in adults with T2DM. Our primary outcome measures include fasting plasma glucose, fasting serum insulin, and insulin resistance utilizing homeostatic model assessment for insulin resistance (HOMA-IR). Secondary outcome measures include resting systolic BP and endothelium-dependent dilation. Further, we will collect plasma for exploratory proteomic analyses. This trial seeks to establish the cardiometabolic effects of 6 weeks of high-resistance IMST in patients with T2DM.